Repeated bout effect: Research update and future perspective - Nosaka, K.; Saldanha Aoki, M. (Brazilian Journal of Biomotricity, 2011)
Responses to the same exercise are never the same, which is particularly so for eccentric exercise. Eccentric exercise results in muscle damage when performed by individuals who are unaccustomed to the exercise. However, when the same exercise is performed again within a certain period of time, it does not induce as sever muscle damage as that was induced previously. It looks as if a bout of eccentric exercise induced protective adaptation in the process of recovering from muscle damage. This adaptation is referred to as the repeated bout effect. The protective adaptation against "maximal" eccentric contractions is induced by submaximal eccentric contractions, a small number of eccentric contractions, eccentric contractions at short muscle lengths, or slow velocity eccentric contractions, which induce less muscle damage, as well as low-intensity eccentric contractions that do not induce any muscle damage, or isometric contractions at a long muscle length. The protective effect could last up to several months, but the remaining length of the effect appears to be influenced by the magnitude of muscle damage in the initial bout. It seems that adaptations of muscle fibers and/or connective tissue are responsible for the repeated bout effect, although neural adaptations are not totally discarded, and the underlying mechanisms need to be investigated further. It should be noted that the magnitude of muscle damage can be attenuated by the use of the repeated bout effect more efficiently than any other prophylactic interventions such as nutritional supplementations, and the effect should be considered when designing a study.